PREPL Deficiency: A Homozygous Splice Site PREPL Mutation in a Patient With Congenital Myasthenic Syndrome and Absence of Ovaries and Hypoplasia of Uterus - Yang, Qi; Hua, Rong; Qian, Jiale; Yi, Shang; Shen, Fei; Zhang, Qiang; Li, Mengting; Yi, Sheng; Luo, Jingsi; Fan, Xin (Frontiers in Genetics, 2020)
Abstract. Prolyl endopeptidase-like (PREPL) deficiency (MIM 616224) is a very rare congenital disorder characterized by neonatal hypotonia and feeding difficulties, ptosis, neuromuscular symptoms, cognitive impairments, growth hormone deficiency, short stature, and hypergonadotropic hypogonadism. This syndrome is an autosomal recessive disease resulting from mutations in the PREPL gene. Previous reports have associated PREPL deficiency with only one nucleotide substitution, the deletion of four nucleotides, and eight small microdeletions in the PREPL gene In this study, we used whole exome sequencing (WES) to identify a novel homozygous splicing mutation (c.616 +1G> T) in a 14-year-old Chinese girl with PREPL deficiency. Sequencing of the RT-PCR products from the patient's blood sample revealed that the c.616 +1G> T variant disrupted normal splicing in intron 4 leading to an aberrant inclusion of 43 nucleotides in intron , a frameshift, and premature termination codon. Our patient exhibited several of the common phenotypes, including severe neonatal hypotonia, growth impairment and cognitive problems. However, we also observed several unusual phenotypic characteristics: absence of the ovaries, hypoplasia of the uterus, microcephaly and a short neck in patient is alsoobserved. These results provide further evidence for the involvement of PREPL development of the ovaries and uterus. Our findings may provide further insight into the relationship between the genotype and phenotype in collagen-associated diseasesand improve the clinical diagnosis of Prolyl endopeptidase-like deficiency.